The first complete mitochondrial genome sequence of the common Baya weaverbird (Ploceus philippinus) from southern India - Venkatesh Nagarajan-Radha; Subanithi-Purnima Murugan; Paramanantha Swami Doss Devaraj (Mitochondrial DNA. Part B. Resources)
The common Baya weaverbird, Ploceus philippinus (Linnaeus, 1766), is best known for its nest construction behaviour. Yet, no genomic studies have been conducted on this species to date. We sequenced the mitochondrial genome of P. philippinus sampled from southern India. The circular mitochondrial genome of 16,867 bp contains 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs (12S and 16S subunits), and a non-coding control region. A maximum-likelihood phylogenetic tree analysis placed P. philippinus and P. nigricollis weaverbirds in a separate clade among other bird species. The mitochondrial genome sequence would benefit future genetic studies in weaverbirds.